2008
DOI: 10.1088/1468-6996/9/2/024214
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic elasticity of magnetically ordered agarose gel

Abstract: The physical properties of agarose gel prepared under strong magnetic fields were investigated. The storage modulus was measured by the reflection method with an ultrasonic pulse. The measurement results of the gel's elasticity indicate that agarose gel has anisotropic properties. The elasticity and its anisotropy depend on the concentration of the gel and the magnetic field to which it is exposed. The experimental results indicate that the anisotropic network structure of the gel is induced by the exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The repeatability in compression was also excellent: the load-displacement responses are almost identical for any given concentration. In addition, a recent paper by Yamamoto et al [30] shows that storage modulus of agarose gel is almost linearly dependent on concentration from 0.5% to 5.0%. They used ultrasonic wave propagation method to measure storage modulus.…”
Section: Resultsmentioning
confidence: 98%
“…The repeatability in compression was also excellent: the load-displacement responses are almost identical for any given concentration. In addition, a recent paper by Yamamoto et al [30] shows that storage modulus of agarose gel is almost linearly dependent on concentration from 0.5% to 5.0%. They used ultrasonic wave propagation method to measure storage modulus.…”
Section: Resultsmentioning
confidence: 98%
“…magnets with as trength of less than 1T esla can efficiently orient such an anofiller.E xamples include particles of magnetite, [50][51][52] barium ferrite, [53][54][55] and carbonyl iron [56][57][58] as well as nickel rods [59] and magnetite-coated alumina platelets. [60] Although such weak handheld magnets are generally not enough to orient diamagnetic nanofillers,s uperconducting magnets (with as trength of several Tesla) can efficiently orient them, such as peptide nanofibers, [61][62][63] polysaccharides, [64] functionalized carbon nanotubes, [65] micelles, [66,67] lipid bilayers, [68,69] graphene oxides, [70] and inorganic nanosheets. [71][72][73] Recent progress in superconducting technology has made such strong magnets easily accessible,a nd this method is widely used.…”
Section: Hydrogels With Oriented Nanofillersmentioning
confidence: 99%
“…In It is reported that agarose undergoes magnetic alignment during gelation [15,16]. The origin of the alignment is attributed to a small crystallite that forms a crosslinking point of the gel.…”
Section: T 1 T 2 T 3 T 4 T 5 T 6 T 7 T 8 Tmentioning
confidence: 99%